Survey of full‐scale sidestream enhanced biological phosphorus removal (S2EBPR) systems and comparison with conventional EBPRs in North America: Process stability, kinetics, and microbial populations. (13th September 2019) - Onnis‐Hayden, Annalisa; Srinivasan, Varun; Tooker, Nicholas B.; Li, Guangyu; Wang, Dongqi; Barnard, James L.; Bott, Charles; Dombrowski, Paul; Schauer, Peter; Menniti, Adrienne; Shaw, Andrew; Stinson, Beverly; et al.
Abstract: Sidestream EBPR (S2EBPR) is an emerging alternative process to address common challenges in EBPR related to weak wastewater influent and may improve EBPR process stability. A systematic evaluation and comparison of the process performance and microbial community structure was conducted between conventional and S2EBPR facilities in North America. The statistical analysis suggested higher performance stability in S2EBPR than conventional EBPR, although possible bias associated with other plant‐specific factors might have affected the comparison. Variations in stoichiometric values related to EBPR activity and discrepancies between the observed values and current model predictions suggested a varying degree of metabolic versatility of PAOs in S2EBPR systems that warrant further investigation. Microbial community analysis using various techniques suggested comparable known candidate PAO relative abundances in S2EBPR and conventional EBPR systems, whereas the relative abundance of known candidate GAOs seemed to be consistently lower in S2EBPR facilities than conventional EBPR facilities. 16S rRNA gene sequencing analysis revealed differences in the community phylogenetic fingerprints between S2EBPR and conventional facilities and indicated statistically higher microbial diversity index values in S2EBPR facilities than those in conventional EBPRs. Practitioner Points: Sidestream EBPR (S2EBPR) can be implemented with varying and flexible configurations, and they offer advantages over conventional configurations for addressing the common challenges in EBPR related to weak wastewater influent and may improve EBPR process stability. Survey of S2EBPR plants in North America suggested statistically more stable phosphorus removal performance in S2EBPR plants than conventional EBPRs, although possible bias might affect the comparison due to other plant‐specific factors. The EBPR kinetics and stoichiometry of the S2EBPR facilities seemed to vary and are associated with metabolic versatility of PAOs in S2EBPR systems that warrant further investigation. The abundance of known candidate PAOs in S2EBPR plants was similar to those in conventional EBPRs, and the abundance of known candidate GAOs was generally lower in S2EBPR than conventional EBPR facilities. Further finer‐resolution analysis of PAOs and GAOs, as well as identification of other unknown PAOs and GAOs, is needed. Microbial diversity is higher in S2EBPR facilities compared with conventional ones, implying that S2EBPR microbial communities could show better resilience to perturbations due to potential functional redundancy. Abstract :